KAJIAN POTENSI PENGGUNAAN KOMPOS DARI RESIDU GAS BIO UNTUK PERENCANAAN SOSIALISASI - Sri Pratiwi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2003)
BPPT has conducted Integrated Research on Biogas from night soil. This research has done thought pilot plant in Pondok Pesantren Tebu Ireng Jombang East Java. The product of the biogas pilot plant are compost and methane gas. The using of these products has been researched to the community. The community survey using descriptive methods, has a result that 79.5 % of the respondens said they intend to use composts for their plantation.There fore the application of biogas technology in waste water treatment should be socialized.